THE ROLE OF GEOMATICS IN CULTURAL HERITAGE CONSERVATION (PANGEEA, 2025)
The major aim of this paper is to present a non-destructive method for the cultural heritage assesment. The proposed methodology is based on the combination of topographic surveys, digital photogrammetry and image processing techniques by means of four control points and photographies of the target , that become metric rectified image at any plane defined by the user. There are many reasons and motives for digital modelling of real world objects, including: virtual reconstruction of historical artifacts icons and buildings that no longer or only partially exist, digital documentation for restoration purposes in case of fire, flood, etc.; ability for virtual interaction without the risk of damage; production of e-learning data for educational resources; virtual tourism; virtual museum exhibits; and interactive visualisation of the objects.
Keywords: cultural heritage; digital documentation; three-dimensional model; Râmeţ Monastery